Women and family in the Caribbean : historical and contemporary considerations : with special reference to Jamaica and Trinidad and Tobago - Reddock, Rhoda ed. (CCS [Georgetown]GY, 1994)
Looks at the origins and social structure of the Caribbean family 1838-1950. Examines the changing roles of women and the family 1950-1994. Focuses on two case studies viz 'Street children in Jamaica' and 'Family violence in Trinidad and Tobago in the 1990s'